2019
DOI: 10.1038/s41564-019-0472-z
|View full text |Cite
|
Sign up to set email alerts
|

RocS drives chromosome segregation and nucleoid protection in Streptococcus pneumoniae

Abstract: Segregation of replicated chromosomes in bacteria is poorly understood outside some prominent model strains and even less is known about how it is coordinated with other cellular processes. Here we report that RocS is crucial for chromosome segregation in the opportunistic human pathogen Streptococcus pneumoniae. RocS is membrane-bound and interacts both with DNA and the chromosome partitioning protein ParB to properly segregate the origin of replication region to new daughter cells. In addition, we show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…In S. pneumoniae, ParB interacts with DivIVA during cell division. It has also been shown that ParB participates in specific crosstalk between DNA segregation, cell division, and capsule formation in this organism [168,170]. S. pneumoniae's incomplete Par(A)B-parS system consists of four parS sites close to oriC, as well as an orphan parB gene [197].…”
Section: Parb's Role In Capsule Formation In S Pneumoniaementioning
confidence: 99%
See 1 more Smart Citation
“…In S. pneumoniae, ParB interacts with DivIVA during cell division. It has also been shown that ParB participates in specific crosstalk between DNA segregation, cell division, and capsule formation in this organism [168,170]. S. pneumoniae's incomplete Par(A)B-parS system consists of four parS sites close to oriC, as well as an orphan parB gene [197].…”
Section: Parb's Role In Capsule Formation In S Pneumoniaementioning
confidence: 99%
“…The deletion of parB impairs chromosome segregation but only in a minor way and has no influence on bacterial growth [71]. Recent reports have shed light on the role of S. pneumoniae ParB, showing that it cooperates with two proteins, CpsD and RocS [168,170]. Capsular polysaccharide protein D (CpsD), a ParA-like ATPase, is a component of a protein complex involved in the synthesis and export of capsular polysaccharide.…”
Section: Parb's Role In Capsule Formation In S Pneumoniaementioning
confidence: 99%
“…Recent studies identified another ParB interacting partner in S. pneumoniae-the RocS protein. RocS is required for chromosome segregation but also interacts with FtsZ and CspD (Mercy et al, 2019). The above examples show that chromosome segregation and cell division are coupled due to the interactions of segregation proteins.…”
Section: Interactions Between Segregation and Cell Division Proteinsmentioning
confidence: 91%
“…In model species, spatiotemporal control of cell division often invokes a negative regulator that prevents division at a given time and/or place in the cell. For instance, nucleoid occlusion factors hinder division over non-partitioned chromosomes (Wu and Errington, 2004;Bernhardt and de Boer, 2005;Mercy et al, 2019), whereas the Min system inhibits division at cell poles (Raskin and de Boer, 1997). A few proteins that positively regulate the localization of the cytokinetic protein FtsZ have also been discovered recently (Willemse et al, 2011;Treuner-Lange et al, 2013;Fleurie et al, 2014;van Raaphorst et al, 2017;Eswara et al, 2018).…”
Section: Spatiotemporal Control Of Non-binary Cell Divisionmentioning
confidence: 99%